Does diversification lead to better loan portfolio returns? Empirical evidence from Indonesian banks - Atahau, A.; Cronje, Tom (De La Salle University Press, 2017)
The composition of the loan portfolios of Indonesian banks are analysed in this study to determine whether loan diversification or loan focus strategies lead to better loan portfolio returns. This study is based on secondary data obtained from the Indonesian Banking Directory of the Indonesian Central Bank, as well as commercial bank annual reports provided by Infobank magazine and the Indonesian Banking Development Institute. Data pertaining to 109 commercial banks for the period 2003 to 2011 were analysed using non-parametric testing of means and panel data regression. The research findings indicate that the loan portfolios of government-owned, domestic-owned, and foreign-owned banks in Indonesia differ in terms of the extent of their diversification to different economic sectors. Furthermore, a significant positive relationship exists between economic sector loan diversification and loan portfolio returns. However, similar results were not found for loan type diversification.